Plateformisation de la mobilité et territorialisation des plateformes : le cas du free-floating en Île-de-France - Timothée Mangeart (Netcom)
Driven by venture capital funded-platforms, shared micromobility has rapidly developed over the second part of the 2010s in the form of free-floating vehicle-sharing. What changes are brought about by the development of free-floating platforms? Based on a case study of Île-de-France (Paris region) and 35 interviews with stakeholders, the study reveals a dual mechanism that goes along the rollout of free-floating services: the platformization of mobility, and the territorialization of platforms. Free-floating platforms operations rely on the uninterrupted presence of their vehicles in the streets associated with the display of vehicles data on dedicated digital applications. The vehicles’ presence in the streets led to a regulation of free-floating platforms by local authorities. Paradoxically, this regulation led to an increase of free-floating platforms influence over the street space: drawing on their superior digital skills, free-floating platforms have extended the scope of geofencing, a technology previously used for operational purposes, and demonstrated their ability to control the presence of their vehicles in the street space.